Pengaruh Motivasi Kerja, Kompetensi dan Kompensasi Terhadap Kinerja Dosen - Wati, Enny (FEB Universitas Lakidende, 2020)
This study aims to determine the effect of work motivation, competence, and compensation on the performance of case study lecturers at Lakidende University in Konawe Regency, Southeast Sulawesi Province. The population in this study were all Permanent Lecturers of the Foundation at Lakidende University, with a sample of 29 people who were obtained by setting 25 percent of the population proportionally divided into 6 faculties. By using multiple linear regression analysis, the results of the study showed that simultaneously motivation, competence, and compensation variables had a positive and significant effect on the performance of the Foundation Permanent Lecturers at Lakidende University. Partially, motivation variable has a negative and not significant effect on the variable performance of Permanent Lecturers at the University of Lakidende, Competency variables have a positive and significant effect on the variable performance of Permanent Lecturers at the University of Lakidende and the compensation variable has no significant effect on the variable performance of the Foundation Permanent Lecturers at the University of Lakidende